IN THE MATTER OF A PETITION BY: INTERNATIONAL BROTHERHOOD ELECTRICAL WORKERS LOCAL UNION 1245 - ASHTON,E; BRANTLEY,JF; DONNELLY,W; GREENBERG,A; JABLONSKY,SA; OHARA,GP; PETERS,J; RODRIGUEZ,RJ (Tufts Archival Research Center, 2007)
Marginalia; Petition proposal decision from the California Occupational Safety and Health Standards Board. Summarizes the requested regulation, which includes the need for acceptable ventilation standards. Emphasizes the growing problems with indoor air pollution and increases in employee complaints. Expresses concern with poor building design in terms of ventilation and recirculation of air. Recognizes that suggestions for improving indoor air quality (IAQ) may be beyond the powers of the Standards Board and therefore will convene an advisory committee to address the issues raised by petitioners.